Climate border adjustments and WTO law extending the EU emissions trading system to imported goods and services - Will, Ulrike (Nijhoff international trade law series ;, 2019)
In Climate Border Adjustments and WTO Law, Ulrike Will develops a convincing reform proposal for a climate border adjustment (BA) on imports within the EU Emission Trading System (ETS). The proposed framework offers a realistic approach which would be immune to disputes at the WTO and comply with international climate agreements while remaining economically feasible and straightforward to implement. The book offers a comprehensive analysis of the WTO cases that might have parallels to the unresolved case of BAs. It provides interpretations of vague legal terms of the applicable WTO agreements and guidance on how to balance between environmentally related and trade liberalising WTO rules. Typified constellations of BAs pave the way for a reform of the EU ETS Directive. The inclusion of legal findings in the context of economic theory and climate science allows for a meaningful discussion of the functioning of the BA, relevant markets and competitive effects of specific design proposals. The proposed framework also takes into account the prevention of extra-jurisdictional effects.